A Standard for the Scholarly Citation of Archaeological Data as an Incentive to Data Sharing. Issue 2 (5th April 2018) - Marwick, Ben; Birch, Suzanne E. Pilaar
ABSTRACT: How do archaeologists share their research data, if at all? We review what data are, according to current influential definitions, and previous work on the benefits, costs, and norms of data sharing in the sciences broadly. To understand data sharing in archaeology, we present the results of three pilot studies: requests for data by e-mail, review of data availability in published articles, and analysis of archaeological datasets deposited in repositories. We find that archaeologists are often willing to share but that discipline-wide sharing is patchy and ad hoc. Legislation and mandates are effective at increasing data sharing, but editorial policies at journals lack adequate enforcement. Although most of the data available at repositories are licensed to enable flexible reuse, only a small proportion of the data are stored in structured formats for easy reuse. We present some suggestions for improving the state of date sharing in archaeology; among these is a standard for citing datasets to ensure that researchers making their data publicly available receive appropriate credit. Abstract : ¿Cómo comparten los arqueólogos sus datos de investigación, si lo hacen? Revisamos qué datos son, de acuerdo con las actuales definiciones influyentes, y el trabajo previo sobre los beneficios, costos y estándares de intercambio de datos en las ciencias en general. Para comprender el intercambio de datos en arqueología, presentamos los resultados de tres estudios piloto: solicitudes de datos por correo electrónico; revisión de la disponibilidad de datos en artículos publicados y análisis de conjuntos de datos arqueológicos depositados en repositorios. Encontramos que los arqueólogos están a menudo dispuestos a compartir, pero el intercambio de toda la disciplina es desigual y ad hoc. La legislación y los mandatos son eficaces para aumentar el intercambio de datos, pero las políticas editoriales de las revistas carecen de aplicación adecuada. Aunque la mayoría de los datos disponibles en repositorios están autorizados para permitir la reutilización flexible, sólo una pequeña proporción de los datos se almacena en formatos estructurados para su fácil reutilización. Presentamos algunas sugerencias para mejorar el estado de la fecha de intercambio en arqueología, incluyendo un estándar para citar conjuntos de datos para asegurar que los investigadores que hacen sus datos disponibles públicamente reciben crédito apropiado.